2013
DOI: 10.3813/aaa.918594
|View full text |Cite
|
Sign up to set email alerts
|

Recreating the Sound of Stonehenge

Abstract: Stonehenge is the largest and most complex ancient stone circle known to mankind. In its original form, the concentric shape of stone rings would have surrounded an individual both visually and aurally. It is an outdoor space and most archaeological evidence suggests it did not have a roof. However, its large, semi-enclosed structure, with many reflecting surfaces, would have reflected and diffracted sound within the space creating an unusual acoustic field for the Neolithic Man.This project has reconstructed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 5 publications
0
8
0
1
Order By: Relevance
“…Further study by the author [35,36] analysed the acoustics present in the final arrangement of the original complete monument, pointing out low frequency resonances, echoes, and reverberation. Field studies by the author with the acoustics researcher Bruno Fazenda [37,38], analysed the Maryhill Monument, a full-size concrete Stonehenge model in the United States, which has an approximately similar design. That research identified higher reverberation than in the remaining monument, and a powerful low frequency resonance at 47-48 Hz; similar low frequency modal effects are discussed further below.…”
Section: Stonehengementioning
confidence: 99%
See 1 more Smart Citation
“…Further study by the author [35,36] analysed the acoustics present in the final arrangement of the original complete monument, pointing out low frequency resonances, echoes, and reverberation. Field studies by the author with the acoustics researcher Bruno Fazenda [37,38], analysed the Maryhill Monument, a full-size concrete Stonehenge model in the United States, which has an approximately similar design. That research identified higher reverberation than in the remaining monument, and a powerful low frequency resonance at 47-48 Hz; similar low frequency modal effects are discussed further below.…”
Section: Stonehengementioning
confidence: 99%
“…The acoustics of the later (final) modelled arrangement of the site, Stonehenge C, dated c.2200 BC, has been examined in earlier publications by this author and Fazenda [35][36][37][38]. Those papers used various theoretical approaches to explore the acoustics of the site, as well as acoustic field tests at a full-size concrete replica that has a design based on Stonehenge, the Maryhill Monument in Washington State, USA.…”
Section: Early Decay Timementioning
confidence: 99%
“…Numerous examples can be found in the literature where alternative sound sources were used. Some examples and the sources that were used are: The measurement of impulse responses in open-air theatres (firecracker) [44,45], in churches (pistol shots and balloons) [46], in Buddhist temples (balloons) [47], measuring the acoustics of catacombs (balloons and firecrackers) [48,49], measurements in Stonehenge (balloons) [50], measurements in the Notre-Dame cathedral (balloons) [51], measurements in the Hagia Sofia (balloons) [52], measurements in urban environments (pistol shots) [53], green roofs absorption (pistol shots) [54], measurements in subway stations (firecrackers) [55], the acoustic of caves (balloons) [56,57], room acoustics (handclap) [58], barrier attenuation (shotshell primer) [59] and classroom acoustics [60] (wooden clapper). The reason that prompted the use of these alternative sources will be presented in the following related chapters.…”
Section: Aim Of This Reviewmentioning
confidence: 99%
“…We can find many approaches that have been used for the acoustic reconstruction of buildings and events as examples of integration of acoustic environments. In Fazenda and Drumm (2011), the authors study the acoustics of Stonehenge. In Collecchia et al (2012), the authors make a computational model of Chavín de Huántar in Peru to study an acoustical problem in the building.…”
Section: Related Workmentioning
confidence: 99%